1995
DOI: 10.1055/s-2007-1000400
|View full text |Cite
|
Sign up to set email alerts
|

Defibrotide®Reduces Monocyte PAI-2 and Procoagulant Activity

Abstract: Defibrotide is a polydeoxyribonucleotide-derived anti-ischemic drug with multiple sites of action involving both plasmatic and cellular targets. This agent has been demonstrated to produce profibrinolytic, cytoprotective, and vaso-facilatory actions. Since monocytes are increased in the mediation of some of the pathophysiologic responses seen in ischemic disorders, the functional properties of these cells were investigated in experimental conditions to evaluate their behavior during resting and stimulated stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Therefore, it has been used in the treatment of many vascular diseases, and is a promising treatment of HSOS. The suggested mechanisms of action of DT include: (i) stimulation of endothelial‐cell release of t‐PA; (ii) up‐regulation of the release of nitric oxide, prostacyclin (PG I2), prostaglandin E2, thrombomodulin and t‐PA both in vitro and in vivo ; (iii) decreased release of plasminogen activator inhibitor‐1; and (iv) stimulation of the adenosine receptor 145–152 . Moreover, DT has been shown to decrease thrombin generation, tissue factor expression and endothelin activity 153–157 …”
Section: Treatmentmentioning
confidence: 99%
“…Therefore, it has been used in the treatment of many vascular diseases, and is a promising treatment of HSOS. The suggested mechanisms of action of DT include: (i) stimulation of endothelial‐cell release of t‐PA; (ii) up‐regulation of the release of nitric oxide, prostacyclin (PG I2), prostaglandin E2, thrombomodulin and t‐PA both in vitro and in vivo ; (iii) decreased release of plasminogen activator inhibitor‐1; and (iv) stimulation of the adenosine receptor 145–152 . Moreover, DT has been shown to decrease thrombin generation, tissue factor expression and endothelin activity 153–157 …”
Section: Treatmentmentioning
confidence: 99%
“…Only one study has shown an increase of fibrinolytic activity by HUVEC alone, as measured by the shortening of the euglobulin lysis time, a test measuring the overall fibrinolytic activity. 18 Other in vitro studies have focused on DF effects on platelet and leukocyte hemostatic properties, [34][35][36][37] or on thrombomodulin expression by HUVEC. 19 This is the first report on the impact of DF in vitro on endothelial procoagulant (TF) and fibrinolytic proteins (PAI-1 and t-PA).…”
Section: Discussionmentioning
confidence: 99%
“…DEF, thanks to its multiple-sites activity, seems to be an ideal drug. Particularly, it acts on: endothelial cells (stimulation, production and balance of PGI 2 , PGE 2 and thrombomodulin; stimulation and release of tPA; inhibition of PAI; modulation of Endothelin-1 release); platelets (reduced adhesion and aggregation due to AMPc increase; reduction of molecular markers of spontaneous microaggregation as thromboglobulin, BTC and plasmatic factor 4); red blood cells (increased deformability; increase of PO 2 and reduction of PCO 2 ); monocytes and polymorphonucleates (reduced production of free radicals; reduced formation of lymphocytes' macroaggregates) (O'Brien et al 1984;Schror et al 1989;Violi et al 1989;Berti et al 1994;Zhou et al 1994;Abbate et al 1995).…”
Section: Discussionmentioning
confidence: 99%